Helicobacter pylori infection as a potential risk factor for multiple sclerosis. (October 2020) - Kountouras, Jannis; Papaefthymiou, Apostolis; Gavalas, Emmanuel; Polyzos, Stergios A.; Boziki, Marina; Kyriakou, Panagiota; Katsinelos, Panagiotis; Zavos, Christos; Liatsos, Christos; Tzivras, Dimitri; Tzitiridou-Chatzopoulou, Maria; Dardiotis, Efthymios; et al.
Abstract: Helicobacter pylori infection ( Hp- I) has been associated with a wide spectrum of gastrointestinal and extra-digestive manifestations, including neurodegenerative diseases. Contradictory data have been published on Hp -I and multiple sclerosis (MS) association, with studies mainly using serology for Hp -I detection that cannot distinguish between active and past infections. We herein hypothesize that humoral and cellular immune responses induced by active Hp -I, beyond damaging locally the gastric mucosa, they may shape the character of systemic autoimmune responses, contributing to MS pathogenesis. To investigate our hypothesis, active Hp -I has been diagnosed in two small MS Greek cohorts by using primarily gastric mucosa histology. A higher prevalence of active Hp -I was documented in MS patients vs. controls (86.4 vs. 50%, P = 0.002) accompanied by exclusive existence of duodenal ulcer and autoimmune diseases with endoscopic and histological findings of chronic active gastritis for the MS group. Our preliminary data suggested that active Hp- I unlike other studies, may not protect, but contribute to MS and we proposed possible  Hp -relating mechanisms involved in MS pathophysiology, that merit further evaluation.